Tackling post-COVID-19 pandemic food crises through the adoption of improved maize seeds and technologies by smallholder farmers: The case of Ejura Sekyeredumase in Ghana - Quarshie, Philip Tetteh; Antwi-Agyei, Philip; Suh, Neville N.; Fraser, Evan D. G. (Frontiers in Sustainable Food Systems, 2022)
Amidst the covid-19 pandemic, the need to accelerate food production efforts to achieve the UN SDG two, i.e., zero hunger target by 2030, is gaining momentum across the global food security discourse. One way to accelerate food production is to adopt improved seeds and technologies that may close existing yield gaps and support food security efforts in regions such as Sub-Saharan Africa. This paper uses mixed methods, including key informant interviews, structured household questionnaire surveys and focus group discussions, to examine the factors influencing the adoption of improved seeds and complementing technologies in Ghana. In particular, we draw insight from theories of failed market-induced behaviour, innovation diffusion and induced-innovation theories to explore farmers' perceptions and adoption of different specific improved maize varieties and technologies for agricultural productivity. Our findings suggest that the level of awareness of improved seeds, particularly hybrid seeds and technologies, and the adoption rate of these technologies are low among Ghana's rural farmers. The findings reveal that socio-demographic and economic factors such as gender, age, cost of seeds, the promise of more yields, market access, social networks' influence, seed availability and accessibility are essential determinants of adopting improved planting technologies among smallholder farmers. This paper argues that location and context-specific-targeted extension services delivery to enhance the widespread adoption of improved seeds and technologies across scales can build farmers' capacity to increase agricultural productivity.